Thermal properties of oil palm lignocellulosic fibre reinforced polymer composites: A comprehensive review on thermogravimetry analysis - M. R. M. Asyraf; N. M. Nurazzi; M. N. F. Norrrahim; K. Z. Hazrati; Muhammad Aizat Abd Ghani; F. A. Sabaruddin; S. H. Lee; S. S. Shazleen; M. R. Razman (Springer Nature, 2023)
Oil palm fibre (OPF) is abundant in resources since it is easily obtained in many parts of an oil palm crop. The application of OPF in polymer composite could provide good mechanical stiffness and strength, and the material is considered environmentally friendly. Research has been carried out on oil palm biocomposites to characterise the thermal, mechanical, and physical behaviours in many conditions. Today, oil palm biocomposites are very limited to producing conventional products, such as brooms and furniture, despite their excellent thermal stability in replacing synthetic fibres. Hence, the TGA and DTG analyses are vital to evaluate the thermal stability of single fibre oil palm fibre reinforced polymer composites in thermoplastic and thermoset matrices. Previous literature established that most biocomposites improved thermal stability depending on specific fibre compositions, surface treatments, fillers, and coupling agents. Nevertheless, a few studies have reviewed the thermal properties of oil palm biocomposites. Thus, this state-of-the-art review article targets to provide baseline knowledge for all material designers, engineers, and manufacturers in choosing suitable matrices for oil palm biocomposites for thermal applications in the automotive, naval, aerospace, and locomotive sectors.